Headache, Loss of Smell, and Visual Disturbances: Symptoms of SARS-CoV-2 Infection? A Case Report. Issue 4 (17th February 2023) - Maselli, Filippo; Storari, Lorenzo; Mourad, Firas; Barbari, Valerio; Signorini, Manuel; Signorelli, Francesco
Abstract: Objective: The purpose of this case report is to describe the main components of the history and physical examination that led to idiopathic intracranial hypertension differential diagnosis, which initially was investigated as COVID-19. Methods (Case Description): A 28-year-old woman complaining of constant headache and loss of smell and taste was suspected as SARS-CoV-2 infection by her general practitioner. She underwent 3 molecular swab tests, all negative, then decided to seek her physical therapist for relieving headache. Results: The full cranial nerve examination revealed impaired olfactory (CNI), abducens (CN VI), and facial (CN VII) nerves, leading the physical therapist to refer the patient to a neurosurgeon for a suspected central nervous system involvement. The neurosurgeon prescribed a detailed MRI and an ophthalmologic examination, which allowed for the final diagnosis of idiopathic intracranial hypertension. Conclusion: An urgent lumbo-peritoneal shunting surgery resolved the patient's symptoms and saved her sight. Despite the ongoing COVID-19 pandemic, health care professionals must pay attention to properly investigating patients' signs and symptoms using comprehensive clinical reasoning, considering the screening for referral to specialist medical attention. Impact: A thorough physical examination is required for every patient even if patients' signs and symptoms are in line with apparent common and widespread pathologies. Cranial nerve evaluation is an essential component of the physical therapist assessment and decision-making process. The ongoing pandemic highlighted the fundamental assistance of physical therapists toward physicians in the screening and management of musculoskeletal diseases.